2015
DOI: 10.1073/pnas.1424980112
|View full text |Cite
|
Sign up to set email alerts
|

CD14 dependence of TLR4 endocytosis and TRIF signaling displays ligand specificity and is dissociable in endotoxin tolerance

Abstract: Dimerization of Toll-like receptor 4 (TLR4)/myeloid differentiation factor 2 (MD2) heterodimers is critical for both MyD88-and TIRdomain-containing adapter-inducing IFN-β (TRIF)-mediated signaling pathways. Recently, Zanoni et al. [(2011) Cell 147(4):868-880] reported that cluster of differentiation 14 (CD14) is required for LPS-/Escherichia coli-induced TLR4 internalization into endosomes and activation of TRIF-mediated signaling in macrophages. We confirmed their findings with LPS but report here that CD14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 44 publications
(56 reference statements)
8
107
1
3
Order By: Relevance
“…When surface CD14 is degraded by gingipains, tolerance can become solely dependent on TLR4 signaling and, thus, can be reversed by anti-TLR4. In contrast, endotoxin tolerance induced by Salmonella-derived LPS is additionally mediated by TLR4-independent CD14 signaling and therefore might not be inhibited solely by TLR4 antagonism (62,63).…”
Section: Discussionmentioning
confidence: 96%
“…When surface CD14 is degraded by gingipains, tolerance can become solely dependent on TLR4 signaling and, thus, can be reversed by anti-TLR4. In contrast, endotoxin tolerance induced by Salmonella-derived LPS is additionally mediated by TLR4-independent CD14 signaling and therefore might not be inhibited solely by TLR4 antagonism (62,63).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the dynasore appeared toxic to the cells at this concentration (data not shown). Previous studies showed the involvement of dynamin in TLR4 internalization (12,40), and the dynamin-dependent process is a crucial part of the LBP-mediated TLR4 internalization mechanism; however, it is difficult to completely exclude the possibility of a dynamin-independent process. As reported previously (13,24), membrane expression of CD14 was required for TLR4 internalization.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-induced TLR4 internalization was reportedly mediated by GTPase dynamin, which is involved in most endocytic processes (12,40). Therefore, we investigated whether dynamin is also involved in the process of LBP-mediated TLR4 internalization.…”
Section: Lbp Mediates Lps-induced Tlr4 Internalization and Signalingmentioning
confidence: 99%
“…Low concentrations of LPS require CD14 to activate MyD88-dependent pathway, but high concentrations (>10 ng/ml) of LPS activate MyD88-dependent pathway even in the absence of CD14 [13, 14]. To induce endocytosis of activated TLR4 linked to activation of TRAM-TRIF pathway, however, LPS requires CD14 even at high concentrations [13, 14]. …”
Section: Introductionmentioning
confidence: 99%